Growing of Yellow Fish Bread, Maize and Soybean to White Mice - SHAGTI, INDHIRA (Poltekkes Kemenkes Kupang, 2017)
Background: Calcium deficiency in human body intake will cause abnormalities of metabolism in the body especially in a nutrient-prone age that is during infancy until the age of children as well as pregnant and lactating women. The content of calcium is large enough in yellow bone meal bone is expected to be one of the alternative fulfillment of body calcium intake. This study aims to know the effect of feeding formula from bone meal of yellow fish and Corn Flour of Yellow and Soybean Meal to blood calcium level in Rat. Methods: This research is an experimental research conducted in the laboratory. The design used is Completely Randomized Design. Results: Average baseline blood calcium levels (h to 0) of the JG1 group (1.31), JG2 (1.42), KD1 (1.33), KD2 (1.40) and Control (1.33) mmol / L. The absorption of calcium in the highest rats at 6th hour after being given the treatment of cornflour + TTIBK. In this study, it was found that the highest levels of calcium in the blood were treated with the JG2 formula and the lowest in the control treatment, where the p-value (0.022) <0.05, which means that the blood calcium levels in the treatment were significantly different. The weight of experimental mice during the study was a possible reduction due to stressful rats due to blood drawn so that appetite decreased. Conclusion: Of these treatments showed the higher intake of calcium will lose weight of rats / lower body fat of mice.